Inverse Association Between Resting-State Putamen Activity and Iowa Gambling Task Performance in Patients With Obsessive-Compulsive Disorder and Control Subjects - Hasuzawa, Suguru; Tomiyama, Hirofumi; Murayama, Keitaro; Ohno, Aikana; Kang, Mingi; Mizobe, Taro; Kato, Kenta; Matsuo, Akira; Kikuchi, Kazufumi; Togao, Osamu; Nakao, Tomohiro (Frontiers in Psychiatry, 2022)
Background: Symptoms of obsessive-compulsive disorder (OCD) have been conceptualized as manifestations of decision-making deficits. Patients with OCD exhibit impairment during the decision-making process, as assessed by the Iowa Gambling Task (IGT). This impairment is independent of clinical severity and disease progression. However, the association between the decision-making deficit and resting-state brain activity of patients with OCD has not been examined. Methods: Fifty unmedicated patients with OCD and 55 matched control subjects completed IGT. Resting-state brain activity was examined using the fractional amplitude of low-frequency fluctuations (fALFFs). fALFF analysis focused on the slow-4 and 5 bands. Group comparisons were performed to determine the association between IGT performance and fALFFs. Results: There was a significant group difference in the association between the IGT total net score and slow-4 fALFFs in the left putamen (voxel height threshold of p< .001; cluster size threshold of p< .05; family wise error-corrected). Higher putamen slow-4 fALFFs were correlated with lower IGT scores for OCD patients (r= -.485; p< .0005) and higher IGT scores for control subjects (r= .402; p< .005). There was no group difference in the association between the IGT total net score and slow-5 fALFFs. Conclusions: These findings in unmedicated patients demonstrate the importance of resting-state putamen activity for decision-making deficit associated with OCD, as measured by IGT. The inverse correlation may be explained by the hypersensitive response of the putamen in patients with OCD.